A fluorine-modulated bulk-phase heterojunction and tolerance factor for enhanced performance and structure stability of cesium lead halide perovskite solar cells. Issue 27 (21st June 2018) - Fu, Lin; Zhang, Yanan; Chang, Bohong; Li, Bo; Zhou, Shujie; Zhang, Luyuan; Yin, Longwei
Abstract : The α-/δ-phase heterojunction induced by fluorine builds a matched band structure, exhibiting a champion PCE of 10.26% with improved stability. Abstract : Although significant progress has been made on the performance of inorganic–organic perovskite solar cells (PSCs), the commercialization of these PSCs is seriously hampered by their poor thermal/moisture stability. Inorganic cesium-based perovskites with relatively high phase stability are ideal alternatives although they still suffer from low photoelectrical conversion efficiency (PCE). Herein, for the first time, fluorine (F) was introduced into the X-site of ABX3 to modulate bulk-phase heterostructures and tolerance factors of inorganic CsPbBrI2− x F x with significantly enhanced PCE and stability. The α-/δ-phase heterojunction is beneficial for efficient dissociation of excitons and charge transport driven by the matched energy band offsets. The lifetime of charge carriers is prolonged due to the retarded charge recombination, which is evidenced by time resolved photoluminescence results; this results in improved short-circuit current density ( J SC ). In view of the Goldschmidt tolerance factor, partial substitution of iodine by fluorine (with a smaller ionic radius) in the ABX3 structure enlarges the inadequate index to stabilize the α-CsPbBrI2 structure. The CsPbBrI1.78 F0.22 PSC with an optimized α-/δ-phase heterostructure displays a superior PCE of up to 10.26% and structural stability against moisture and time. This study sets up a new avenue for designing high-performance PSCs for potential industrial applications.